Rehabilitation of coral reefs through removal of macroalgae: state of knowledge and considerations for management and implementation. Issue 5 (1st August 2018) - Ceccarelli, Daniela M.; Loffler, Zoe; Bourne, David G.; Al Moajil‐Cole, Grace S.; Boström‐Einarsson, Lisa; Evans‐Illidge, Elizabeth; Fabricius, Katharina; Glasl, Bettina; Marshall, Paul; McLeod, Ian; Read, Mark; Schaffelke, Britta; et al.
Abstract : Coral reef ecosystems are under increasing pressure by multiple stressors that degrade reef condition and function. Although improved management systems have yielded benefits in many regions, broad‐scale declines continue and additional practical and effective solutions for reef conservation and management are urgently needed. Ecological interventions to assist or enhance ecosystem recovery are standard practice in many terrestrial management regimes, and they are now increasingly being implemented in the marine environment. Intervention activities in coral reef systems include the control of coral predators (e.g. crown‐of‐thorns starfish), substrate modification, the creation of artificial habitats and the cultivation, transplantation, and assisted recruitment of corals. On many coastal reefs, corals face competition and overgrowth by fleshy macroalgae whose abundance may be elevated due to acute disturbance events, chronic nutrient enrichment, and reduced herbivory. Active macroalgae removal has been proposed and trialed as a management tool to reduce competition between algae and corals and provide space for coral recruitment, in the hope of restoring the spatial dominance of habitat‐forming corals. However, macroalgae removal has received little formal attention as a method of reef restoration. This review synthesizes available knowledge of the ecological role of macroalgae on coral reefs and the potential benefits and risks associated with their active removal.